THE ROLE OF UMMI KALSUM ISLAMIC BOARDING SCHOOL IN THE DEVELOPMENT OF ISLAMIC EDUCATION IN GUNUNGSITOLI - Mawaddah, Mawaddah; Hanum OK, Azizah; Budianti, Yusnaili (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the social condition of Islamic education in Gunungsitoli, the contribution of the Ummi Kalsum Islamic Boarding School in Islamic Education in Gunungsitoli, and the involvement of alumni of the Ummi Kalsum Islamic Boarding School in the development of Islamic and social education in Gunungsitoli. The method used in this study is a qualitative method with a phenomenological approach. Data collection techniques with observation, interviews, and document studies. The results of the research in this thesis first; highlight that the development of Islamic education in Gunungsitoli is not as fast as in areas with a majority Muslim population. The main factor influencing this is Gunungsitoli's status as an area with a minority Muslim population, which makes Islamic education have to compete with other education systems that may be more dominant. In this context, the biggest challenge is how to increase the attractiveness of Islamic education in the midst of the diversity of society. Second; the contribution of the pesantren extends to the surrounding community through various service activities. Pesantren actively organizes programs such as religious counseling, social service skills training, and community-based economic empowerment activities. These activities are designed to provide real benefits to the community, while strengthening the role of pesantren as a center for the development of the people. Third; the contribution of alumni who return to Gunungsitoli to teach, become religious leaders, and support the construction of Islamic boarding schools. Alumni of the pesantren function as a liaison that strengthens the social network between the pesantren and the community.